Implementasi Supervisi Pendidikan Dalam Penerapan Triple Kurikulum di SDIT Al-Irsyad Al-Islamiyyah Pamekasan - Akbar, Khairu Ramadanal; Buna'i (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
Supervision is carried out as a form of business sign to find out that all activities are running according to their duties and functions as well as anticipating if there are problems that need to be fixed. In an educational institution, especially one based on Islam, supervision is carried out as a form of supervision for the school principal in monitoring an activity whether the activity is running as it has been predetermined. Based on this, research was carried out at SDIT Al-Irsyad Al-Islamiyyah Pamekasan regarding the implementation of educational supervision in implementing the triple curriculum consisting of three research focuses, namely: 1) How is the implementation of educational supervision in implementing the triple curriculum at SDIT Al-Irsyad Al-Islamiyyah Pamekasan; 2) What factors support and hinder the implementation of educational supervision in implementing the triple curriculum at SDIT Al-Irsyad Al-Islamiyyah Pamekasan; 3) What is the impact of educational supervision on the implementation of the triple curriculum at SDIT Al-Irsyad Al-Islamiyyah Pamekasan.